Integrating Critical Thinking in an English Speaking Coursebook Speak Now 1 : A Bloom’s Taxonomy-Based Evaluation - Setiawan, Wawan; Surista, Ade (Jurnal Paedagogy, 2025)
This study evaluates the integration of critical thinking skills in the Speak Now 1 English coursebook, specifically in the context of the STBA JIA Basic Speaking course. A mixed-method approach was employed, including qualitative content analysis of 32 speaking activities and a quantitative survey analysis involving 41 students. The speaking activities were analyzed using the revised Bloom's Taxonomy to determine the cognitive domains involved and the questionnaire was gauged students’ views on the integration of critical thinking through frequencies and percentages. The findings revealed that all six cognitive domains were present in the coursebook with “understanding” accounting for the largest percentage, followed by “applying”, and “creating” and the least prevalent domains were “evaluating” and “analyzing”. Meanwhile, students displayed positive perceptions of incorporating critical thinking into the coursebook. However, the study found that the cognitive domains of speaking activities were not structured hierarchically according to a hierarchical system of the revised Bloom’s Taxonomy and that higher-order thinking skills (HOTS) were underutilized. The study suggests that teachers could equip the coursebook with additional tasks targeting “analyzing” and “evaluating” domains and it highlights the importance of balancing cognitive domains in speaking coursebooks in order to promote critical thinking skills in speaking classes.